Considerations on the basis of medical reasoning for the use in AI applications - Koumpis, Adamantios; Graefe, Adam S. L. (Frontiers in Medicine, 2024)
We discuss the integration of Artificial Intelligence and Machine Learning in medical reasoning and decision-making, with a focus to the challenges and opportunities associated with the massive consumption of data required for training AI systems and contrast this with the limited data typically available to medical practitioners. We argue for a balanced approach that includes small data and emphasize the importance of maintaining the art of clinical reasoning amidst technological advancements. Finally, we provide, related to the complexities of medical reasoning, the potential of multidisciplinary research, and the necessity for careful abstraction and conceptual modeling in AI applications.